(untitled) (Journal of Human Sciences, 2022)
Ahmed al-Sharif left Libya for the Ottoman Empire as a result of the siege imposed by Britain and prevented him from entering the eastern region. During his stay there, Britain followed Ahmad al-Sharif and placed him under scrutiny because he posed a danger to his presence in Iraq, especially as he sought to create a broad Islamic front that includes the Arabian Peninsula, the Levant and Iraq and Morocco in order to address colonial influence. After the end of World War I, Britain took advantage of Mustafa Kemal Ataturk’s desire to hold negotiations with her about Turkey’s status and independence. During these negotiations, the British Foreign Secretary set his conditions for this independence: that Turkey sever its connection with the Islamic world, that the Islamic caliphate be abolished, and that Turkey pledge to put down every movement It is carried out by the supporters of the Caliphate, and for Turkey to choose a civil constitution for it instead of the Ottoman constitution, whose provisions are derived from Islamic Sharia, so Ataturk agreed to that and abolished the Islamic Caliphate. Ahmed Al-Sharif did not remain silent about these developments. Rather, he addressed Ataturk saying to him: “We did not support you and stand with you except for the sake of preserving the entity of the Islamic religion. legitimacy and political system of Islamic rule” At that time, Ahmed Al-Sharif realized that he no longer had a place in the state of Ataturk, and the effect of leaving for Syria occupied by France, and on the day following his arrival on November 5, 1924 AD, Ahmed Al-Sharif visited the British Consulate and submitted an application for an entry visa to Egypt After the British government refused Ahmed Al-Sharif’s request for permission to travel to Egypt, the commander (Tommy Martin), head of the French Political Bureau, sent in mid-December 1924 AD to Ahmed Al-Sharif asking him to leave Syria. Ahmed Al-Sharif left Syria for the Hijaz to stay in the hospitality of Abdul Aziz Al Saud. Since his arrival in the Hijaz, Ahmad Al-Sharif has been placed under surveillance and all requests submitted by Ahmad Al-Sharif to travel to Egypt or Sudan were rejected. The Italian Consul in Jeddah also expressed his fears, stressing that the Italian government fears his arrival in Libya through Sudan, and Ahmed Al-Sharif remained besieged in the Hijaz until his death.